PENGORGANISASIAN PELATIHAN OLEH KELOMPOK PENYANYI JALANAN (KPJ) KOTA BENGKULU - Kendey Kendey; Rizkan Rizkan; Ririn Gusti (Jurnal Pendidikan Sepanjang Hayat, 2020)
This research is aimed to know organizing training by Kelompok Penyanyi Jalanan (KPJ) Bengkulu City. The subjects of this research are four people, that is Andi as chairman of the KPJ Bengkulu City, Nita as a member of the KPJ Bengkulu City, Herman and Heri as a street child who was fostered by KPJ Bengkulu City. The method used in this research is qualitative method. The technique of collecting data used interview, observation and documentation. The data analysis techniques used data reduction, data presentation and conclusion retractation. The validity check used triangulation technique which starts from the triangulation of subject, triangulation of time and triangulation of technic.  From research result, Organizing carried out by the Kelompok Penyanyi Jalanan (KPJ) Bengkulu City has been carried out. This can be seen by the organizational structure that has been compiled, which is then for each individual involved in it charged with duties and responsibilities in accordance with positions they have agreed upon previously. Keywords: , Organizing, Training, Groups,